2022
DOI: 10.1055/a-1756-3879
|View full text |Cite
|
Sign up to set email alerts
|

Der Erfinder der „Triage“ – Dominique-Jean Larrey (1766–1842), Napoleons oberster Militärchirurg

Abstract: ZusammenfassungDominique-Jean Larrey (1766–1842) war leitender Chirurg der französischen Armee unter Kaiser Napoleon I. Er ist als Vater der modernen Militärchirurgie sowie der Entwicklung des „Triagesystems“ bekannt geworden. Larrey war ein hervorragender und engagierter Arzt, der nicht nur die eigenen, sondern auch die Soldaten der gegnerischen Truppen medizinisch versorgt hat. Beim Fehlen einer zuverlässigen Analgesie und Anästhesie war zu damaliger Zeit die Geschwindigkeit und das Können das hervorstechend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Wartime has always triggered important surgical progress for the care of the wounded, 75 such as the invention of the ambulance for the triage of war casualties by Dominique-Jean Larrey, chief military doctor in French emperor Napoleon's army. 76 At this time, and owing to the peculiar bone anatomy of the craniocervical junction and the precise course of the lower CN through the cranial base and along the jugulo-carotid gutter, a few authors have reported specific eponym combinations of CN deficits:…”
Section: Historical Contextmentioning
confidence: 99%
“…Wartime has always triggered important surgical progress for the care of the wounded, 75 such as the invention of the ambulance for the triage of war casualties by Dominique-Jean Larrey, chief military doctor in French emperor Napoleon's army. 76 At this time, and owing to the peculiar bone anatomy of the craniocervical junction and the precise course of the lower CN through the cranial base and along the jugulo-carotid gutter, a few authors have reported specific eponym combinations of CN deficits:…”
Section: Historical Contextmentioning
confidence: 99%